2021
DOI: 10.1037/pas0001035
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Fearlessness about Death Scale in adolescents.

Abstract: Recent theories of suicide behavior have proposed a risk factor that differentiates suicide ideators from suicide attempters: Suicide capability. Fearlessness about death, one component of capability, has predicted the likelihood of a future attempt in adult samples. Although there is preliminary evidence about its value in youth, the fearlessness about death scale (FAD) has not yet been validated in clinical adolescents. We sought to examine the psychometric properties of this scale in adolescents at high ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
9

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 27 publications
0
4
0
9
Order By: Relevance
“…FAD reliability in our sample was strong (Cronbach's α = 0.85). The scale has shown strong convergent and discriminant validity in young adults (Ribeiro et al, 2014), and recently shown invariance across age, sex, and time in adolescents (Krantz et al, 2021).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…FAD reliability in our sample was strong (Cronbach's α = 0.85). The scale has shown strong convergent and discriminant validity in young adults (Ribeiro et al, 2014), and recently shown invariance across age, sex, and time in adolescents (Krantz et al, 2021).…”
Section: Methodsmentioning
confidence: 99%
“…A recent study found that the FAD predicted adolescent attempts during and in the short term following treatment for suicidal thoughts and behaviors, while controlling for other frequently cited risk variables (Ferm et al, 2020). Most recently, the scale's psychometric properties were validated in adolescents (Krantz et al, 2021). Additional investigations have shown invariance across suicide attempt history and in‐ versus outpatient status in adolescents (Yang et al, in review).…”
Section: Interpersonal‐psychological Theory Of Suicide and Fadmentioning
confidence: 99%
“…Al respecto, el Acquired Capability for Suicide Scale -Fearlessness About Death (ACSS-FAD) es una versión reducida de la escala original de Capacidad Adquirida para el Suicidio (Ribeiro et al, 2014). El ACSS-FAD evalúa específicamente la intrepidez ante la muerte y ha sido adaptado en Alemania, Corea del Sur, Italia y Estados Unidos (Krantz et al, 2021;Magliocca et al, 2022;Seo & Kwon, 2017;Spangenberg et al, 2016). De acuerdo con los antecedentes, la población objetivo de estudio estuvo mayormente constituida por estudiantes universitarios de diferentes carreras profesionales (Magliocca et al, 2022;Seo & Kwon, 2017).…”
Section: Introductionunclassified
“…De acuerdo con los antecedentes, la población objetivo de estudio estuvo mayormente constituida por estudiantes universitarios de diferentes carreras profesionales (Magliocca et al, 2022;Seo & Kwon, 2017). Un estudio se basó en población general de adolescentes, adultos jóvenes y mayores (Spangenberg et al, 2016) y otro estudio en población clínica adolescente con antecedentes de conductas suicidas (Krantz et al, 2021). Respecto del enfoque y análisis estadístico, los cuatro países realizaron sus resultados a partir de la teoría clásica de los test (TCT) mediante las técnicas de análisis factorial confirmatorio, relación con otras variables y confiabilidad con los coeficientes omega y alfa; sin embargo, solo Estados Unidos analizó la estabilidad temporal de la confiabilidad (Krantz et al, 2021).…”
Section: Introductionunclassified
See 1 more Smart Citation